Determinants for receiving the seasonal influenza vaccine during the COVID-19 pandemic in the United Arab Emirates: 10.55131/jphd/2023/210110 - Marzooqi, Nada Al; AlJasmi, Laila; AlShehhi, Badreya; AlNahas, Sawsan; Hassan, Mohamed Badi; Zahran, Mohamed; Khalil, Marwa (Journal of Public Health and Development, 2022)
Influenza is considered a major health problem in the whole world today. Vaccination is an effective way to prevent infection and decrease mortality of lots of infectious diseases like influenza. The current COVID 19 pandemic has imposed a risk of coinfection by both SARS-CoV-2 and influenza virus. The concern is that a more severe influenza season will overwhelm already strained health systems. This study aims at exploring the attitudes and beliefs related to vaccine uptake, and to identify the underlying barriers to the intention to get vaccinated. This is a cross sectional study. An anonymous electronic questionnaire was distributed. The questionnaire includes questions based on the context of the Health Belief Model. Chi-square test and regression analysis were applied to test the association between variables and the intention to vaccinate. A total of 7574 participants were included in the study. Females represented 57% of the respondents. Those who were 35-44 years, male, Emirati national, retired, married, graduates and with a previous history of taking the influenza vaccine were significantly associated with higher intentions to vaccinate. The perceived benefits, susceptibility and severity of the disease were motivators for taking the vaccine. Psychological and physical barriers were significantly affecting the intention to vaccinate. Protecting the family and community and recommendations by health care providers were the most important cues for action. Physical and psychological barriers to influenza vaccine uptake need to be addressed and tackled. The current study calls for attention to the importance of the role of health care providers’ recommendations for getting vaccinated.